2005
DOI: 10.1117/12.617362
|View full text |Cite
|
Sign up to set email alerts
|

Development of grazing-incidence multilayer mirrors by direct Ni electroforming replication: a status report

Abstract: The Ni electroforming replication process has been used successfully by Beppo-SAX, JET-X/SWIFT, and XMMNewton, to produce their gold-coated X-ray mirrors. The important feature of the technique is that, also with thin substrates, it is possible to achieve a good angular resolution, which is important for obtaining high signal-to-noise ratios in deep observations and imaging extended sources, while the assembly and integration of the monolithic shells is a relatively easy task. Two approaches can be used for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…We have shown that the PANTER X-ray Test Facility is not only well-suited for the calibration and characterisation of short focal length X-ray mirror performance parameters like effective Reflectivity R(parabola) × R(hyperbola) as function of energy for a Pt/C multilayer shell, with model (solid line) for incidence angles of 0.257 • and 0.129 • , respectively [8] area and half-energy width in the "classical" soft X-ray range (up to 15 keV). It can very well also be used for longer focal lengths (here: 10 m) where the mirror sample will be put into the vacuum tube.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that the PANTER X-ray Test Facility is not only well-suited for the calibration and characterisation of short focal length X-ray mirror performance parameters like effective Reflectivity R(parabola) × R(hyperbola) as function of energy for a Pt/C multilayer shell, with model (solid line) for incidence angles of 0.257 • and 0.129 • , respectively [8] area and half-energy width in the "classical" soft X-ray range (up to 15 keV). It can very well also be used for longer focal lengths (here: 10 m) where the mirror sample will be put into the vacuum tube.…”
Section: Discussionmentioning
confidence: 99%
“…photons are reflected at the paraboloid but do not hit the hyperboloid anymore and thus do not reach the focal point. These effects, however, can be calculated and taken into account when analysing the calibration data [8]. Figure 4 shows a NiCo replicated shell with W/Si multilayer coating (MSFC+SAO) mounted on a spider, just at the entry of the PANTER vacuum tube to the instrument chamber.…”
Section: Multi-layer Mirror Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group is the only one that uses CN x to coat and smooth the mandrel (see Ulmer et al (2003) and references therein), but the multilayer coating process we developed has been copied by at least one other group (i.e. Pareschi et al, 2005). This process is to coat a mandrel with multilayer, electroform over these layers, and then remove the electroformed multilayers with layers intact on the inside of the mirror.…”
Section: Multilayersmentioning
confidence: 99%
“…The PANTER X-ray facility now allows testing in soft (0.2 ÷ 10 keV) and hard (15 ÷ 50 keV) X-rays multilayer-coated optics prototypes for future X-ray telescopes (Pareschi et al 2005;Romaine et al 2005). The source distance finiteness causes some departures of the optic performances, with respect to the case with the source at astronomical distance: effective area loss, different incidence angles on paraboloid and hyperboloid, focal length displacement, a slight focal spot blurring (Van Speybroeck & Chase 1972).…”
Section: Introductionmentioning
confidence: 99%